Legal Policy of Pretrial Arrangements in Criminal Procedure Law in Indonesia by the Constitutional Court - Daswanto Daswanto (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
This research examines the legal policy direction of pretrial arrangements in Indonesia's criminal procedure law, focusing on Constitutional Court Decisions Number 21/PUU-XII/2014, 102/PUU-XIII/2015, and 66/PUU-XVI/2018. These decisions have significantly shaped the evolution of pretrial provisions, ensuring alignment with constitutional principles of justice, legal certainty, human rights protection, and simple, fast, low-cost justice. Through normative legal research employing statutory, conceptual, and case-based approaches, the study analyzes how the Constitutional Court's rulings address ambiguities in existing norms, enhance judicial oversight, and strengthen the protection of suspects' rights. Findings indicate that the Constitutional Court’s decisions aim to refine pretrial norms by expanding judicial authority, clarifying procedural ambiguities, and balancing human rights protection with efficient judicial processes. The research underscores the role of legal politics in harmonizing criminal procedural law with evolving societal and legal demands, offering insights for further reforms to uphold justice and human dignity. Future research could explore comparative analyses, implementation challenges, and the integration of digital technologies to enhance the efficiency and equity of pretrial systems.